Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
y = x + 1
Step-by-step explanation:
The gradient of a line can be defined by the equation:
m (gradient) = (y1 – y2 ) ÷ (x1 – x2) ----> "1" and "2" should be in subscript
For (-7,-6) we use x2 and y2 (because this point can be anywhere along a line):
x2 = -7, y2 = -6
Plug these values into the formula above:
m = (y-(-6)) ÷ (x-(-7))
m = (y+6) ÷ (x+7)
At this stage, the equation can't be solved as there are two unknowns. Therefore, the gradient must be found another way. Two lines are parallel if they have the same gradient - in their y=mx+c equations, m will be equal.
x - y=7 is the line alluded to in the question. Rearranging this equation into the line equation format gives:
y = x-7 ---> The gradient (coefficient of x) is 1.
Therefore, the gradient of the other parallel line must also be 1.
This can be substituted into the previous equation to give:
1 = (y+6)÷(x+7)
x+7 = y+6
x+1 = y
Therefore, the answer is y=x+1
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.